Greater Beta-Adrenergic Receptor Mediated Vasodilation in Women Using Oral Contraceptives - Limberg, Jacqueline K.; Peltonen, Garrett L.; Johansson, Rebecca E.; Harrell, John W.; Kellawan, Jeremy M.; Eldridge, Marlowe W.; Sebranek, Joshua J.; Walker, Benjamin J.; Schrage, William G. (Frontiers in Physiology, 2016)
Background: β-adrenergic receptors play an important role in mitigating the pressor effects of sympathetic nervous system activity in young women. Based on recent data showing oral contraceptive use in women abolishes the relationship between muscle sympathetic nervous system activity and blood pressure, we hypothesized forearm blood flow responses to a β-adrenergic receptor agonist would be greater in young women currently using oral contraceptives (OC+, n=13) when compared to those not using oral contraceptives (OC-, n=10). Methods: Women (18-35 years) were studied during the early follicular phase of the menstrual cycle (days 1-5) or placebo phase of oral contraceptive use. Forearm blood flow (FBF, Doppler ultrasound) and mean arterial blood pressure (MAP, brachial arterial catheter) were measured at baseline and during graded brachial artery infusion of the β-adrenergic receptor agonist, Isoproterenol (ISO), as well as Acetylcholine (ACH, endothelium-dependent vasodilation) and Nitroprusside (NTP, endothelium-independent vasodilation). Forearm vascular conductance was calculated (FVC = FBF/MAP, ml/min/100mmHg) and the rise in FVC from baseline during infusion quantified vasodilation (∆FVC = FVCinfusion – FVCbaseline). Results: ISO increased FVC in both groups (p<0.01) and ISO-mediated ∆FVC was greater in OC+ compared to OC- (Main effect of group, p=0.02). Expressing data as FVC and FBF resulted in similar conclusions. FVC responses to both ACH and NTP were also greater in OC+ compared to OC-. Conclusions: These data are the first to demonstrate greater β-adrenergic receptor-mediated vasodilation in the forearm of women currently using oral contraceptives (placebo phase) when compared to those not using oral contraceptives (early follicular phase), and suggest oral contraceptive use influences neurovascular control.